Proapoptotic Bax and Bak proteins form stable protein-permeable pores of tunable size - Bleicken, Stephanie; Landeta, Olatz; Landajuela, Ane; Basañez, Gorka; García-Sáez, Ana J. (The journal of biological chemistry, 2013)
The Bcl-2 proapoptotic proteins Bax and Bak mediate the permeabilization of the mitochondrial outer membrane during apoptosis. Current models consider that Bax and Bak form pores at the mitochondrial outer membrane that are responsible for the release of cytochrome c and other larger mitochondrial apoptotic factors (i.e. Smac/DIABLO, AIF, and endoglycosidase G). However, the properties and nature of Bax/Bak apoptotic pores remain enigmatic. Here, we performed a detailed analysis of the membrane permeabilizing activity of Bax and Bak at the single vesicle level. We directly visualized that cBid-activated Bax and BakΔC21 can form membrane pores large enough to release not only cytochrome c, but also allophycocyanine, a protein of 104 kDa. Interestingly, the size of Bax and BakΔC21 pores is not constant, as typically observed in purely proteinaceous channels, but evolves with time and depends on protein concentration. We found that Bax and BakΔC21 formed long-lived pores, whose areas changed with the amount of Bax/BakΔC21 but not with cardiolipin concentration. Altogether, our results demonstrate that Bax and BakΔC21 follow similar mechanisms of membrane permeabilization characterized by the formation of protein-permeable pores of dynamic size, in agreement with the proteolipidic nature of these apoptotic pores.
Gesehen am 27.11.2020